EXPLORING A COMPREHENSIVE NEEDS ANALYSIS FOR TEACHING ENGLISH IN THE HOTEL AND HOSPITALITY INDUSTRY. - Wahyu, Gede Eka; Susanta, I Putu Agus Endra (Jurnal Review Pendidikan dan Pengajaran, 2025)
Acquiring proficiency in a foreign language is essential for everyone. The competitive nature of the global job market sets specific competency expectations for applicants, particularly within the hotel and hospitality sector, where at a minimum, proficiency in one foreign language is expected. This study aimed to analyze the needs of students learning a foreign language, with a focus on English for specific purposes. A mixed-method approach was employed for this research. The participants in this study comprised 50 students. Data was collected through a series of questionnaires and interview forms. The findings of the study are presented through tables and descriptive explanations. According to the study, 54.55% of learners indicated that they study English for career purposes, while 45.45% expressed a desire to improve their speaking abilities. The challenges faced by language learners included the opinion of 36.36% who reported insufficient grammar knowledge, followed by 35.35% who cited a lack of confidence or fear of making mistakes while speaking in English. Furthermore, regarding the four language skills that participants aimed to master, 57.57% expressed the goal of being able to communicate effectively in English, with 36.36% wanting to enhance their public speaking skills in English.